PENGARUH PERSEPSI HARGA, PROMOSI, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE (Studi Pada Konsumen Di Konter Sinarmas 1 Plasa Simpang Lima Semarang) - Muhammad Azwar Anas, 12.05.51.0094; Tjahjaningsih, Endang. (Students' Journal of Economic and Management, 2018)
The purpose of this study was to determine and analyze the influence of perceptions of price, promotion, and service quality on the decision to purchase mobile phones in Sinarmas 1, Simpang Lima Plaza Semarang. In this study independent variables that influence purchasing decisions are limited to variable perception of price, promotion and service quality. The population in this study were consumers who had bought a cellphone at the Sinarmas 1 counter, Simpang Lima Semarang Plaza. And as many as 96 respondents were selected as samples. Data testing techniques used include validity test, reliability test, multiple linear regression test, determination coefficient and hypothesis testing which includes F test and t test. The test results obtained that partially variable price perception has a positive and significant effect on purchasing decisions. Promotion variables have a positive and significant effect on purchasing decisions. Service quality variables have a positive and significant effect on purchasing decisions. Keywords: Perception of Price, Promotion, Service Quality and Purchase Decision